Flipbook as a Learning Medium: A Study on Indonesian ESP Students - Darmawan, Iwan; Heriyawati, Dwi Fita; Mustofa, Mutmainnah; Romadhon, M Galuh Elga (VELES Voices of English Language Education Society, 2024)
Technological advancements are significantly transforming the landscape of Indonesian education, shifting from traditional methods to digital learning media. This study examines the adoption of Flipbook, a digital tool, in English for Specific Purposes (ESP) courses, aiming to enhance the learning experience for students enrolled in English language study programs. Utilizing Flipbook as an instructional medium, lecturers anticipate offering a novel approach to integrating technology in education. Data were gathered through questionnaires administered to seventy-six students focusing on ESP materials. The questionnaire, comprising thirty-one items with both positive and negative statements, evaluated four key aspects: the completeness of the learning content delivered through Flipbook, student engagement in learning activities, the effectiveness of lecturers in managing the digital learning environment, and the adequacy of facilities and infrastructure supporting the use of Flipbook. The findings demonstrated varying levels of effectiveness: The lecturer's ability to manage Learning was notably effective, with a high mean score of 44.97, indicating that Flipbook facilitates dynamic classroom management. Learning Activities also showed positive outcomes, with a mean score of 36.43, suggesting satisfactory engagement and interactivity. However, Learning Completeness and Facilities and Infrastructure highlighted areas needing improvement, with mean scores of 31.57 and 27.24, respectively. These lower scores reveal significant gaps in content delivery completeness and the supporting infrastructure, which are critical for effectively using digital learning tools.